Current State of Logistics Development and Its Role in the China’s Regional Economy - Xiaomei Sun; Amangeldi Zhumadilov; Madina Myrzalieva; Avaz Kazakov; Aigerim Akmatova (Qubahan Academic Journal)
In modern conditions logistics plays a particularly important role in the context of the development of the country, as it allows more effective development of other areas of economic activity of the country due to the speed and quality of movement of goods or people. This study examined this area in China in comparison with data from Kyrgyzstan. The main methods used during the study were analysis, historical method, forecasting, comparison. The study investigated the role of logistics in regional development, drawing on the experience of Kyrgyzstan and China. The objectives of regional development policy were shown at the beginning, emphasizing the importance of a balanced distribution of resources and economic activities between regions. Logistics becomes a key factor in achieving these goals, ensuring connectivity, economic growth, and efficiency in resource allocation. Furthermore, the paper analyzed the unique challenges and opportunities faced by Kyrgyzstan in the logistics sector. For this, the study also considered selected statistical data that can characterize this area. The paper also presented comparative data of China’s logistics industry, demonstrating its complexity and crucial role in global trade. Assessing the country’s experience, strategic ideas for improving the logistics industry in Kyrgyzstan were also presented, which included many diverse types of recommendations. The study brings new knowledge in the field of logistics for its development in the country, as well as provides an opportunity to assess the state of these areas in China and Kyrgyzstan.